2012
DOI: 10.1063/1.4734344
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry preserving parameterization schemes

Abstract: Methods for the design of physical parameterization schemes that possess certain invariance properties are discussed. These methods are based on different techniques of group classification and provide means to determine expressions for unclosed terms arising in the course of averaging of nonlinear differential equations. The demand that the averaged equation is invariant with respect to a subalgebra of the maximal Lie invariance algebra of the unaveraged equation leads to a problem of inverse group classifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 59 publications
0
69
0
Order By: Relevance
“…1,2 Nowadays, there has been growing interest in studying the variable-coefficient NLEEs, which are often considered to be more realistic than their constantcoefficient counterparts in modeling a variety of complex nonlinear phenomena under different physical backgrounds. [3][4][5][6][7][8][9][10][11] Since those variable-coefficient NLEEs are of practical importance, it is meaningful to systematically investigate completely integrable properties such as bilinear forms, Lax pairs, bilinear Bäcklund transformations, infinite conservation laws and various exact analytic solutions. The Bell T.-T. Zhang et al polynomials are found to play an important role in the characterization of the integrability of NLEEs.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Nowadays, there has been growing interest in studying the variable-coefficient NLEEs, which are often considered to be more realistic than their constantcoefficient counterparts in modeling a variety of complex nonlinear phenomena under different physical backgrounds. [3][4][5][6][7][8][9][10][11] Since those variable-coefficient NLEEs are of practical importance, it is meaningful to systematically investigate completely integrable properties such as bilinear forms, Lax pairs, bilinear Bäcklund transformations, infinite conservation laws and various exact analytic solutions. The Bell T.-T. Zhang et al polynomials are found to play an important role in the characterization of the integrability of NLEEs.…”
Section: Introductionmentioning
confidence: 99%
“…The representation (11) implies that X 1 1 = X 2 2 = |T t | 1/2 cos θ and X 1 2 = −X 2 1 = −|T t | 1/2 sin θ, which means that transformation components X 1 and X 1 satisfy the Cauchy-Riemann system…”
Section: Equivalence Groupoidmentioning
confidence: 99%
“…A number of classes of differential equations that are important for applications are normalized or specifically semi-normalized or can be partitioned into normalized classes and hence were classified within the framework of the algebraic method. See, e.g., [1,7,11,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigations of Hamiltonian dynamics and Lie algebra are major theoretical developments under the present COST Action [106][107][108][109][110]. In general, symmetries of differential equations are fundamental constraints on how physically self-consistent parameterizations must be constructed for a given system.…”
Section: Non-mass Flux Based Approaches: New Theoretical Ideasmentioning
confidence: 99%